2018
DOI: 10.1007/s11845-018-1797-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute hospital reconfiguration and self-harm presentations: a before-and-after study

Abstract: There is evidence to suggest that acute hospital reconfiguration of hospital services impacts on patterns of patient flow. Findings have implications for those implementing reconfiguration of acute services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It can be hypothesised that when ED services are halted or reduced in one location, nearby hospitals can expect to see pressures on patient flows from the ED to in-patient beds unless capacity is increased in the new destination hospital. In Ireland, there is evidence to suggest that the reconfiguration of hospital services has impacted on patterns of patient flow specifically for those presenting with self-harm in the Mid-West 35. EDs that are geographically further from the closed ED would also be expected to be less impacted by an increase in the number of attendances from that hospital 34.…”
Section: Introductionmentioning
confidence: 99%
“…It can be hypothesised that when ED services are halted or reduced in one location, nearby hospitals can expect to see pressures on patient flows from the ED to in-patient beds unless capacity is increased in the new destination hospital. In Ireland, there is evidence to suggest that the reconfiguration of hospital services has impacted on patterns of patient flow specifically for those presenting with self-harm in the Mid-West 35. EDs that are geographically further from the closed ED would also be expected to be less impacted by an increase in the number of attendances from that hospital 34.…”
Section: Introductionmentioning
confidence: 99%
“…Studies employing these designs have primarily utilised hospital records and data recorded via self-harm registries. [13][14][15][16][17][18][19] However, a systematic review that examined aspects of routine clinical care following self-harm (eg, hospital admission or specialist follow-up) found little evidence for their role in reducing repeat self-harm and suicide, 20 despite evidence from individual studies being used to inform several guidance. 21 22 The reasons for a lack of evidence from observational studies may reflect the size and representativeness of the samples used, the quality of study design, as well as the consistency, quality and range of outcomes used.…”
Section: Open Accessmentioning
confidence: 99%
“…While initiatives such as this have the potential to increase the provision of evidence-based care, their outcomes have been under-researched. 21 22 Some recent natural experiment studies have shown how changes in service delivery impact on patterns of self-harm, including hospital reconfiguration 23 and expansion of liaison psychiatry services. 24 25 However, there are virtually no studies examining the impact of national programmes for the clinical management of self-harm in hospital settings.…”
Section: Introductionmentioning
confidence: 99%